Digitalization of Human Resource Management: Business Governance Toward an Advanced Indonesia - Dismas Persada Dewangga Pramudita (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
The digitization of Human Resource Management (HRM) is an important catalyst in promoting sustainable business in the digital economy era. This qualitative article examines how the digital transformation of HRM (digital HRM) contributes to business sustainability through practices such as HR analytics, e-HR platforms, GHRM (green HRM), and algorithmic/AI-driven HRM. Using a qualitative approach based on meta-synthesis of literature and thematic analysis of recent international studies, the article presents a framework of the relationship between HRM digitalization, organizational capacity to manage human resources sustainably, and its implications for national development (Indonesia Maju). Findings indicate that HRM digitalization improves operational efficiency, supports the development of employees' digital competencies, and enables the monitoring of social performance through data mechanisms, but also poses ethical risks, algorithmic bias, and cultural adoption challenges. To realize this potential in Indonesia, integrative policies are needed in the form of strengthening the digital literacy of the workforce, ethical data governance, and the integration of sustainability principles in the design of digital HR policies. This article concludes the importance of policy recommendations and research agendas to guide HRM digitalization as a driver of sustainable business towards an advanced Indonesia.